Conditions and Needs for Organizing Music Activities to Promote Well-being of the Elderly in Thailand - Pantasri, Yotsapan; Keanamponpan, Pornpan; Vatanasapt, Patravoot (Parichart Journal, 2023)
The purpose of this research article is to study the conditions and needs for organizing music activities to promote the health of the elderly in Thailand. By collecting quantitative research data. (Quantitative data) and qualitative (Qualitative Research) results are presented using descriptive analysis methods. The results of the research found that: 1. Conditions for organizing music activities to promote the health of the elderly in Thailand. It has the most characteristics of conditions for organizing music activities. 26.98% are musical activities involving physical movement and music, consisting of aerobic activities, dancing, bass lob and dancing. Followed by music listening activities at 20.98 percent, followed by singing activities at 20.59 percent, mostly karaoke singing and musical instrument practice activities at 10 percent. 2. The need for organizing music activities to promote the health of the elderly in Thailand Elderly people have a desire to develop their complete health by encouraging them to practice listening to music, singing, and singing karaoke. Practicing musical instruments and body movement for music The elderly wanted to organize music activities in the senior school more than once per semester, 60.9 percent, and wanted the senior school to include music activities to promote well-being through exercise, 65.6 percent, including aerobics, dancing, and dance. Slob and Ramwong